RETRACTED : Analysis of Service Quality, Payment Procedures and Tax Sanctions on Improving Motor Vehicle Taxpayer Compliance (at the North Medan Samsat Office) - Sarah Monika Napitupulu; Herry Krisnandi; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
The purpose of this study is to analyze Service Quality, Payment Procedures and Tax Sanctions on Taxpayer Compliance at UPT SAMSAT Medan Utara. The data source of this study used primary data obtained by conducting questionnaires and given to respondents. The data analysis method in this study used multiple regression analysis with testing tools using SPSS software version 24. The population used in this study is two-wheeled motor vehicle taxpayers registered with UPT Samsat Medan Utara. Sampling in a study of 100 respondents using the accidental sampling method. The stages of research include descriptive statistics, Validity and Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis and Hypothesis Test. The results of hypothesis testing show that the variables of service quality, payment procedures and tax sanctions have a partial and significant effect on taxpayer compliance.